The origins and Sources of polycyclic Aromatic Hydrocarbons (PAHs) and Aliphatic Hydrocarbons (N-Alkanes) in The Tigris, Euphrates, and Shatt Al-Arab rivers: Asal-usul dan Sumber Hidrokarbon Aromatik Polisiklik (PAH) dan Hidrokarbon Alifatik (N-Alkana) di Sungai Tigris, Eufrat, dan Shatt Al-Arab - Qassem , Mariam A.; Kadhim , Hamzah A.; Al-Hejuje , Makia M. (Universitas Muhammadiyah Sidoarjo, 2024)
Samples were taken from three sites along the Tigris, Euphrates, and Shatt Al-Arab Rivers between November 2022 and July 2023 to ascertain the concentrations, distribution, and sources of PAH compounds and aliphatic hydrocarbons in water samples. Aliphatic (n-alkane) compounds' carbon chain lengths were measured from C7 to C38, and the total amount of n-alkanes in water varied between 48.09 µg/l and 276.98 µg/l. The heavy PAHs were fluoranthene and chrysene, whereas the light PAHs were carbazol and anthracene, with concentrations ranging from 45.16 to 1848.54 ng/l. The LMW/HMW, CPI, and Pristine/Phytoene ratios indicated that n-alkane hydrocarbons were primarily biogenic, pyrogenic, and at least petrogenic. Nonetheless, the LMW/HMW, Phenanthrene/Anthracene, and Flouranthene/Pyrene ratios showed that the primary sources of PAH molecules were petrogenic and pyrogenic environments. Highlights: Samples from Tigris, Euphrates, Shatt Al-Arab analyzed for PAHs, n-alkanes. n-Alkanes (C7–C38) ranged 48.09–276.98 µg/l; PAHs 45.16–1848.54 ng/l. Sources: biogenic, pyrogenic, petrogenic for n-alkanes; petrogenic, pyrogenic for PAHs. Keywords: water, Tigris, Euphrates, N-alkanes, polycyclic aromatic hydrocarbons (PAHs), and Shatt Al-Arab